The Influence of Leadership Style on the Performance of Civil Servants in the Karawang Regency General Election Commission Environment - Susilo, Lantip Handoyo; Wibowo, Endro; Bangkahulu, Jailani; Samsi, Johannes; Azhari, Yasin (Universitas Mohammad Husni Thamrin, 2025)
In realizing good governance, a state apparatus must be able to improve its performance optimally, but this needs to be supported by the existence of quality Human Resources. This study was conducted to analyze the influence of leadership style on the performance of civil servants at the General Election Commission (KPU) of Karawang Regency. The background of this study is based on the important role of a leader in creating an effective work environment, especially in government bureaucracy that demands professionalism, accountability, and transparency. The approach used was quantitative with a descriptive associative design, involving 30 employees as respondents. Data were collected through the distribution of questionnaires that had been tested for validity and reliability, and supported by interviews and field observations. The results of the analysis showed a positive and significant relationship between leadership style and employee performance. The correlation coefficient value of 0.699 indicates that the relationship between the two variables is in the strong category, while the linear regression test revealed that 48.8% of the variation in employee performance can be explained by leadership style. These findings confirm that the more appropriate the leadership style applied, the higher the employee performance. The implications of this research highlight the importance of leadership as a highly strategic factor in improving the performance of state officials. Therefore, the Karawang Regency General Elections Commission (KPU) is advised to continue developing adaptive, communicative, and performance-oriented leadership practices to optimally achieve organizational goals.